Impact of Immune-Related Adverse Events on Efficacy of Immune Checkpoint Inhibitors in Patients with Advanced Hepatocellular Carcinoma - Kennedy Yao Yi Ng (Karger Publishers, 2021)
Introduction: Development of immune-related adverse events (irAEs) has been associated with enhanced efficacy with the use of immune checkpoint inhibitors (ICIs). It remains unknown whether such an association exists in advanced hepatocellular carcinoma (aHCC). This study aims to evaluate the association between irAEs and ICI efficacy in patients with aHCC. Methods: We performed a retrospective cohort study on patients with aHCC who received at least one dose of an ICI between May 2015 and November 2019 at the National Cancer Centre Singapore. The primary study objectives were to compare the overall survival (OS) and progression-free survival (PFS) between patients with and without irAEs. Complementary multivariable landmark analyses were performed at the 6-week and 12-week landmarks. Data cutoff was December 31, 2020. Results: One hundred and sixty-eight patients were included. Median age was 69 years, 85.7% were male, 57.7% had hepatitis B infection, 60.7% had ECOG 0, and 78.0% had Child-Pugh A liver cirrhosis. 82.7% received ICI monotherapy, while 17.3% received ICI in combination. Development and severity of irAE were correlated with survival. The median PFS for grade ≥3 irAE versus grades 1–2 irAE versus no irAE was 8.5 versus 3.6 versus 1.3 mths (p < 0.001). The median OS for grade ≥3 irAE versus grades 1–2 irAE versus no irAE was 26.9 versus 14.0 versus 4.6 mths (p < 0.001). Patients with ≥2 irAEs had a significantly longer OS on multivariable analysis (adjusted hazard ratio [aHR]0.35, p < 0.001). The presence of grade ≥3 irAEs was associated with a significantly longer OS on the multivariable analysis at the 6-week landmark (aHR0.34, p = 0.030) and 12-week landmark (aHR0.28, p = 0.011). The use of systemic corticosteroids in patients with irAE was associated with a trend toward a longer OS (20.7 vs. 14.3 mths, p = 0.064). Conclusion: Our study suggests that the presence of all-grade irAEs may be a potential prognostic biomarker in patients with aHCC treated with ICI. Patients with more severe irAEs and multisystem involvement have better prognosis. The prompt use of systemic corticosteroids to treat patients with irAEs is key to ensure the best long-term outcomes for these patients.